2018
DOI: 10.13057/biodiv/d200127
|View full text |Cite
|
Sign up to set email alerts
|

Body size characteristics and polymorphism in GH and GHRH genes of Simeulue Buffalo of Aceh, Indonesia

Abstract: Eriani K, Rahmi R, Jamil I, Rosnizar R, Azhar A. 2019. Body size characteristics and polymorphism in GH and GHRH genes of Simeulue Buffalo of Aceh, Indonesia. Biodiversitas 20: 236-242. This study was done to determine body size characteristics, to identify the presence of polymorphism in the GH/MspI and GHRH/HaeIII genes, and to analyze the relationship between GH and GHRH gene polymorphisms to body size characteristics in Simeulue buffalo. Experimental animals used were 45 Simeulue buffalo randomly sampled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…However, no statistical significance (P > 0.05) was determined in the Anatolian water buffalo breed. In contrast to this study, various studies conducted on 3 different GH gene regions (exon 5 -Alu I; intron 3 -Msp I; 3'UTR -Hae III) in water buffalo breeds reported them as monomorphic (Mitra et al, 1995;Vataliya, 2014, 2017;Eriani et al, 2019).…”
Section: Discussioncontrasting
confidence: 85%
“…However, no statistical significance (P > 0.05) was determined in the Anatolian water buffalo breed. In contrast to this study, various studies conducted on 3 different GH gene regions (exon 5 -Alu I; intron 3 -Msp I; 3'UTR -Hae III) in water buffalo breeds reported them as monomorphic (Mitra et al, 1995;Vataliya, 2014, 2017;Eriani et al, 2019).…”
Section: Discussioncontrasting
confidence: 85%
“…The lowest coefficient of variation was found in the hind leg length of buffaloes from Lebak district, while the highest coefficient of variation was found in the horn length of buffaloes from the Tangerang District. These coefficients of variation are relatively higher than those of Gojri buffaloes (3.32-19.41%) (Vohra et al 2015), Brazilian buffaloes (3.65-16.68%) (de Melo et al 2018), and Aceh buffaloes (5.39-16.06%) (Eriani et al 2019).…”
Section: Morphometrics Description Of Indigenous Buffaloes Of Bantenmentioning
confidence: 82%
“…The significance of conducting buffalo development research is to fill the gap in the fundamental science behind the diversity of KBuf/TBuf breeds. Previous research only reported the productivity and epidemiology of diseases of buffaloes and provided limited information on genotypic and phenotypic characterization (Eriani et al 2019;Konda et al 2019;Pratama et al 2019;Yaemkong et al 2019;Priyono et al 2018;Terkawi et al 2011;Komariah et al 2014;Chaikhun et al 2010). Therefore, the exploration of phenotypic diversity and variation in KBuf/TBuf is necessary to assess the important aspects suitable for their breeding and development.…”
Section: Introductionmentioning
confidence: 99%